Reconstructing The Development Of The Bantu Final Vowels - Good, Jeff (My University, 2022)
So-called Final Vowel (FV) morphemes are an integral part of the verbal inflectional morphology of most Bantu languages, though relatively little attention has been paid to their historical development in the context of the overall Bantu verbal system. A small set of FVs is reconstructed as appearing at the end of verbs and, along with other morphemes, they play a role in encoding tense, aspect, mood, and polarity. This chapter reconsiders the reconstruction of the Bantu FV system, with the goal of arriving at a better understanding of what the situation may have been like in Proto-Bantu (PB) with respect to these morphemes and how a system of inflectional marking of this kind could have developed. Data is drawn from languages of the north-western Bantu area which have not previously been systematically examined with respect to reconstruction of the FVs. On the basis of data from these languages, it appears that the right edge of the Bantu verb was a more active site for the formation of new morphology than suggested by previous studies and that the standard reconstructions of the FVs may represent a simplification of a more complex PB situation.
Keywords: Bantu; Final Vowel; Reconstruct